Troubled waters : a river's journey toward justice - Weatherford, Carole Boston, 1956- (Bloomsbury Children's Books, 2026)
"From Young People's Poet Laureate Carole Boston Weatherford and award-winning illustrator Bryan Collier, a stirring account of the 1965 Selma to Montgomery marches, as witnessed by the Alabama River." --